Incidence of anemia based on haemoglobin levels in children 2-12 years of aged in Nobel Medical College Teaching Hospital, Biratnagar, Nepal - Sinha, Amar Kumar; Majumdar, Biswajit (Journal of Nobel Medical College, 2012)
Haemoglobin levels were used to estimate the incidence of anaemia in children 2-12 years old in the population of Biratnagar, Morang Dist., Nepal. who were attending Nobel Medical College & teaching hospital. Out of 5063 subjects, 634 children’s were selectively diagnosed as anaemia. Among the 2406 children’s aged 2-6 years 5.4% were diagnosed with mild anaemia,2.7% moderate anaemia and 1.7% severe anaemia (WHO definition) of 2657 children’s aged 7-12 years,10.2% were diagnosed with mild anaemia, 3.1% moderate anaemia and 1.3% severe anaemia. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7297 Journal of Nobel Medical College (2012), Vol.1 No.2 p.36-38